2010
DOI: 10.1159/000316908
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Blood Cell Activation and Complement Activation in Factor VIII and von Willebrand Factor Concentrates

Abstract: SummaryBackground: Preparations of commercially available clotting factor VIII are complex protein mixtures. Most of them contain either von Willebrand factor or human serum albumin as stabilizers. The aim of the study was to quantify further proteins in twelve concentrates either of recombinant origin or derived from human plasma. Methods: Proteins were separated by two-dimensional polyacrylamide gel electrophoresis (2D-PAGE). Some proteins were quantified by ELISA. Results: Recombinant clotting factor prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…As we reported earlier, several plasma-derived FVIII products contain substances that influence platelet activation status and/or inflammation that were absent in recombinant FVIII [21]. Among them was alpha-defensin, a neutrophil cationic peptide, which besides exerting antimicrobial and proinflammatory functions, acts as a potent platelet agonist [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we reported earlier, several plasma-derived FVIII products contain substances that influence platelet activation status and/or inflammation that were absent in recombinant FVIII [21]. Among them was alpha-defensin, a neutrophil cationic peptide, which besides exerting antimicrobial and proinflammatory functions, acts as a potent platelet agonist [20].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we identified up to 0.85 ng/IU of the platelet alpha granule protein CXCL4 as well as platelet-activating substances such as myeloperoxidase and alpha-defensin [20] in some plasma-derived FVIII concentrates [21]. Therefore, we tested the direct effect of FVIII products on differentiation of human macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Three FVIII products were evaluated for their in vitro effects on cell stress sensors: a pdFVIII product with a moderate level of impurities (product 1, Haemoctin®SDH; Biotest Pharma GmbH, Dreieich, Germany), a pdFVIII product with a relatively high level of impurities (product 2, Octanate®; Octapharma GmbH, Langenfeld, Germany) [4,6], and an rFVIII product formulated with sucrose (rFVIII-FS, KOGENATE®; Bayer Pharma AG, Berlin, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…However, other impurities that could affect patient health may be present in pdFVIII products. In an earlier study [4], we identified hematocyte-derived proteins and proteins of the complement activation pathway in several pdFVIII products of varying purities. Proteins isolated in some of the pdFVIII products tested included anaphylatoxin C3a, the platelet activation markers thrombospondin-1 and platelet factor 4, and leukocyte-secreted myeloperoxidase and α-defensin [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation